Smartphone sebagai Akses Sarana Kehidupan dalam Karya Digital Painting - Fiona Puspa Ningrum; Syafei Syafei (Departement of Mathematics Education, 2024)
This final work aims to visualize smartphones as a means of access to life in digital painting works using a contemporary style. The idea for creating this work is a visualization of the use of smartphones whose benefits can be felt in life. The method in the process of creating digital painting works of art goes through several stages, namely: preparation, elaboration, synthesis, concept realization, and completion. Each work has a size of 100cm x 100cm with the title of the work,